Beneficial effects of running and milk protein supplements on Sirtuins and risk factors of metabolic disorders in rats with low aerobic capacity - S. Lensu (Metabolism Open, 2019)
Background: Physical activity and dietary intake of dairy products are associated with improved metabolic health. Dairy products are rich with branched chain amino acids that are essential for energy production. To gain insight into the mechanisms underlying the benefit of the sub-chronic effects of running and intake of milk protein supplements, we studied Low Capacity Runner rats (LCR), a rodent exercise model with risk for metabolic disorders. We especially focused on the role of Sirtuins, energy level dependent proteins that affect many cellular metabolic processes. Methods: Forty-seven adult LCR female rats sedentary or running voluntarily in wheels were fed normal chow and given supplements of either whey or milk protein drink (PD)-supplemented water, or water only for 21 weeks. Physiological responses were measured in vivo. Blood lipids were determined from serum. Mitochondrial markers and Sirtuins (Sirt1-7) including downstream targets were measured in plantaris muscle by western blotting. Results: For the first 10 weeks whey-drinking rats ran about 50% less compared to other groups; still, in all runners glucose tolerance improved and triglycerides decreased. Generally, running induced a ∼six-fold increase in running capacity and a ∼8% decrease in % body fat. Together with running, protein supplements increased the relative lean mass of the total body weight by ∼11%. In comparison with sedentary controls, running and whey increased HDL (21%) and whey, with or without running, lowered LDL (−34%). Running increased mitochondrial biogenesis and Sirtuins 3 and 4. When combined with exercise, both whey and milk protein drink induced about a 4-fold increase in Sirt3, compared to runners drinking water only, and about a 2-fold increase compared to the respective sedentary group. Protein supplements, with or without running, enhanced the phosphorylation level of the acetyl-coA-carboxylase, suggesting increased fat oxidation. Both supplemented diets increased Sirt5 and Sirt7 without an additional effect from exercise. Running diminished and PD supplement increased Sirt6. Conclusion: We demonstrate in rats new sub-chronic effects of milk proteins on metabolism that involve Sirtuins and their downstream targets in skeletal muscle. The results show that running and milk proteins act on reducing the risk factors of metabolic disorders and suggest that the underlying mechanisms may involve Sirtuins. Notably, we found that milk protein supplements have some favorable effects on metabolism even without running. Keywords: Low capacity running rat (LCR), Metabolism, Muscle, Running, Sirtuins, Whey